Consumption of Aloe to improve health outcomes in adults with irritable bowel syndrome: A systematic review and meta-analysis - Fong, Francisco J (Department of Public Health and Family Medicine, 2020)
PART A is a research protocol which describes the background and proposed methodology of this systematic review and meta-analysis. This section details the quantitative and qualitative methods to be used when analysing the effect of Aloe in the treatment of patients with irritable bowel syndrome (IBS). PART B is an extended literature review which expands on some of the topics raised in the background section of the protocol. A more in-depth explanation of the epidemiology of IBS, is presented, as well as the strengths and limitations of current treatment options in order to understand the context around the proposed research. PART C presents this research in the form of a journal manuscript in a format suitable for submission to Plos ONE. This manuscript includes a background to the research followed by the results section which is then discussed. Lastly, implications for clinical practice are posited and suggestions for further research are offered.